Dynamic Alterations of Gut Microbiota in Porcine Circovirus Type 3-Infected Piglets - Hou, Lei; Wang, Jing; Zhang, Wei; Quan, Rong; Wang, Dan; Zhu, Shanshan; Jiang, Haijun; Wei, Li; Liu, Jue (Frontiers in Microbiology, 2020)
Porcine circovirus type 3 (PCV3) is a novel porcine circovirus species associated with several diseases, such as porcine dermatitis and nephropathy syndrome-like clinical signs, reproductive failure, cardiac pathologies, and multisystemic inflammation, in piglets and sows. Currently, many studies are focused on the interaction between gut microbiota composition and the progression of diseases. However, the dynamic alterations in the composition of the gut microbiota following PCV3 infection is still unclear. In this study, alterations in the gut microbiota in piglets with PCV3 infection were analyzed at various time points (7, 14, 21, and 28 dpi) using the Illumina MiSeq platform. Obvious structural segregations were shown with Partial Least Discriminant Analysis (PLS-DA) regarding bacterial diversity and richness between mock-infected piglets and PCV3-infected piglets as well as among 4 different time points. Analysis of the abundances of the gut microbiota constituents revealed that the relative abundances of Parabacteroides and Catenisphaera at 14 dpi and of Blautia, Coprococcus and unclassified_f_Lachnospiraceae at 28 dpi were significantly increased, while the Clostridium_sensu_stricto_1, Ruminococcaceae_UCG-014, Clostridium_sensu_stricto_6 and norank_o_Mollicutes_RF9 abundances at 21 dpi and Clostridium_sensu_stricto_1 and Terrisporobacter abundances at 28 dpi were markedly decreased in PCV3-infected piglets. In addition, significant differences were observed in functional classification based on Cluster of Orthologous Groups (COG) assignment between mock-infected piglets and PCV3-infected piglets. Our findings demonstrated that PCV3 infection caused dynamic changes in the gut microbiota community. Therefore, regulating the gut microbiota community may be an effective approach for preventing PCV3 infection.